Science, public health, and the state in modern Asia - Bu, Liping, 1960-; Stapleton, Darwin H.; Yip, Ka-che, 1944- (London ; New York : Routledge, 2012)
'This book examines the encounter between Western and Asian models of public health and medicine in a range of East and Southeast Asian countries over the course of the twentieth century, in the context of colonial rule, post-colonial development and modern state-building'--
Includes bibliographical references and index.
Keywords: Medicine -- Southeast Asia; Public health -- Southeast Asia; Public health -- East Asia; Medicine -- East Asia